The Potential Identification of Pulau Belimbing Village for the Development of Halal Tourism in Kampar Regency - Angga Pramana; Yelly Zamaya (Jurnal Dakwah Risalah, 2021)
Halal tourism is currently an interesting trend to study. The population of Indonesia, amounting to 273.5 people, of which 87.2 percent are Muslim. This is a huge opportunity for the development of halal tourism. Pulau Belimbing Village is one of the villages in Kampar Regency which has tourist destinations that are synonymous with Islamic customs and religions which can be a site to promote Islamic culture. This research is a qualitative descriptive study that describes the existing conditions of the research object. From the results of this study, it was found that Pulau Belimbing Village has the potential to develop into one of the halal tourism destinations in Kampar Regency and Riau Province. Intense support from the local government and various interested parties is needed to realize this halal tourism.